The “Turn” and Other Turns: Museum Anthropology and Material Culture Studies in Russia - Baranov, Dmitry (Anthropologica, 2022)
Changes of perspective and abrupt revision of the essential disciplinary frameworks are at the root of several turns in the humanities and social sciences (the “material,” “ontological,” and other turns) that have been treated sometimes as mystifications contrary to common sense. In reality, such shifts can be extremely productive in the search for new knowledge. This is particularly important for anthropology, a discipline committed to “crossing borders,” extending beyond the social and the human, and searching for external perspectives from which to interpret human culture. This paper discusses several Russian cases of study on material culture, partly inspired by the acquaintance with alternative (mythological and folklore) ideas about things. Special emphasis is placed on museum studies of material culture. In particular, I address the question of why Russian museum anthropology stubbornly resists attempts to re-evaluate the anthropocentric perspective in materiality studies.